Pengembangan Kemampuan Berpikir Kreatif Mahasiswa melalui Pembelajaran Berbasis Proyek pada Mata Kuliah Kimia Lingkungan di Masa Pandemic Covid 19 - Syarifa Wahidah Al-Idrus; Muti’ah Muti’ah; R. Rahmawati (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2021)
This research aims to develop students' creative thinking skills. This study used a classroom research method with a one-shot case study design. The sample in this study were students of environmental chemistry at the Chemistry Education Study Program, FKIP UNRAM. Observation data will be obtained based on observation sheets to describe student activities and creativity from the beginning of the project to the end of the project. The project that is given focuses on environmental pollution material. The results of this study indicate that students are very active in the project-based learning process. Students' creative thinking skills in designing simple experiments about environmental pollution are in a good and very good position. The generating stage with a value of 90 (very good), the planning stage with a value of 88 (very good), the producing / producing stage is very good (88), the checking stage 80 is good, and the critiquing stage with a value (Good).